2014
DOI: 10.1016/j.bbmt.2014.04.020
|View full text |Cite
|
Sign up to set email alerts
|

Phase I Study of the Safety and Pharmacokinetics of Plerixafor in Children Undergoing a Second Allogeneic Hematopoietic Stem Cell Transplantation for Relapsed or Refractory Leukemia

Abstract: The safety, pharmacokinetics and biological effect of plerixafor in children as part of a conditioning regimen for chemo-sensitization in allogeneic hematopoietic stem cell transplantation (HSCT) have not been studied. This is a phase I study of plerixafor designed to evaluate its tolerability at dose of 0.24 mg/kg given intravenously on day -4 (level 1), day -4, and day -3 (level 2), or day -4, -3, and day -2 (level 3) in combination with fludarabine, thiotepa, melphalan, and rabbit anti-thymocytic globulin f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 23 publications
2
7
0
Order By: Relevance
“…As reported in other trials of plerixafor in children and adults with acute leukemias, 27,28,32 we observed that plerixafor mobilized leukemic blasts into the peripheral blood. Despite heterogeneous expression of surface CXCR4, mobilization occurred in the vast majority of patients in this trial.…”
Section: Discussionsupporting
confidence: 87%
“…As reported in other trials of plerixafor in children and adults with acute leukemias, 27,28,32 we observed that plerixafor mobilized leukemic blasts into the peripheral blood. Despite heterogeneous expression of surface CXCR4, mobilization occurred in the vast majority of patients in this trial.…”
Section: Discussionsupporting
confidence: 87%
“…Also, in a study examining plerixafor administration for allogeneic stem cell transplantation seven of 12 patients had at least one adverse event possibly related to plerixafor. Nausea and vomiting were the most common adverse effect that occurred in patients in this study (occurring in three patients each), as well as in the study reported by Maschan and colleagues …”
Section: Discussionsupporting
confidence: 87%
“…When plerixafor binds to CXCR4, it blocks the binding of its cognate ligand CXCL12, allowing for the mobilization of HSCs out of the marrow . While efficacy of plerixafor has been proven in adult patients, data are limited for efficacy in pediatric patients . Therefore, we conducted a retrospective chart review evaluating the safety and efficacy of plerixafor in pediatric patients.…”
mentioning
confidence: 99%
“…Of the 12 patients enrolled, only two experienced disease relapse post-transplantation and six were alive at a median follow-up of 67 months ( 120 ). In the third trial, plerixafor was included as part of a myeloablative conditioning regimen for 12 pediatric patients with rrAML undergoing a second allogeneic HSCT (NCT01068301) ( 121 ). With a median duration of follow-up of 332 days, four of the 12 patients (33%) were alive with two being disease free.…”
Section: Using Cxcr4 Inhibitors In Myeloablative Chemotherapy Regimenmentioning
confidence: 99%